Rectal trauma in adults. (January 2013) - Barkley, Sarah; Khan, Mansoor; Garner, Jeff
Rectal trauma is associated with high rates of morbidity and mortality and generally affects young males due to its aetiology of violent crime and vehicular collision. Historically, management has followed principles derived from military practice, with faecal diversion, pre-sacral drainage and distal washout being mandatory. Civilian trauma studies examining management of colon and rectum injuries from the early 1950s identified major differences in the level of energy transfer between civilian and military wounds, given that the vast majority are penetrating in nature. This led to a re-evaluation of the necessity for these interventions for all rectal injuries. Current management depends on whether the injury is intra- or extraperitoneal, with those above the peritoneal reflection being readily accessible and amenable to treatment as for colon injury. Extraperitoneal injuries remain difficult to access and direct repair is usually impossible; the mainstay of treatment in most instances remains faecal diversion. The role of pre-sacral drainage and distal washout remains contentious in the realms of civilian rectal injury but retains a place in battlefield or other high-energy transfer rectal injuries where aggressive early management reduces septic complications. This article reviews the historical and current evidence for the management of both civilian and military extraperitoneal rectal injuries.